Correction: Glaser et al., The histone demethylase JMJD2B regulates endothelial-to-mesenchymal transition - Glaser, Simone F.; Heumüller, Andreas W.; Tombor, Lukas; Hofmann, Patrick; Muhly-Reinholz, Marion; Fischer, Ariane; Günther, Stefan; Kokot, Karoline E.; Okada, Hitoshi; Hassel, David; Kumar, Sandeep; Jo, Hanjoong; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2020)
CELL BIOLOGY Correction for “The histone demethylase JMJD2B regulates endothelial-to-mesenchymal transition,” by Simone F. Glaser, Andreas W. Heumüller, Lukas Tombor, Patrick Hofmann, Marion Muhly-Reinholz, Ariane Fischer, Stefan Günther, Karoline E. Kokot, David Hassel, Sandeep Kumar, Hanjoong Jo, Reinier A. Boon, Wesley Abplanalp, David John, Jes-Niels Boeckel, and Stefanie Dimmeler, which was first published February 7, 2020; 10.1073/pnas.1913481117 ( Proc. Natl. Acad. Sci. U.S.A. 117 , 4180-4187). - - The authors note that Hitoshi Okada should be added …